An Intervention to Improve Physical Function and Caregiver Perceptions in Family Caregivers of Persons With Heart Failure. (February 2020) - Gary, Rebecca; Dunbar, Sandra B.; Higgins, Melinda; Butts, Brittany; Corwin, Elizabeth; Hepburn, Kenneth; Butler, Javed; Miller, Andrew H.
Objective: This randomized controlled trial was conducted to determine whether a 12-week home-based aerobic and resistance exercise program would improve physical function and caregiving perceptions among family caregivers (FCGs) of persons with heart failure.Method: Overall, 127 FCGs were randomized to one of three groups: usual care attention control (UCAC), psychoeducation only (PE), and psychoeducation plus exercise (PE + EX). Physical function measures (6-min walk test, handgrip, and upper and lower strength) and caregiving perceptions (Bakas Caregiving Outcomes Scale) were obtained at baseline and at 6 months.Results: FCGs in the PE + EX showed significant improvement in 6-min walk distance ( p = .012), handgrip, and lower extremity strength compared with the PE and UCAC groups. The combined group had the greatest improvement in caregiver perceptions ( p < .001).Conclusion: FCGs in the PE + EX group improved the most in physical function and caregiver perception outcomes. Directions for future research are provided.